Effect of Rainfall Pattern and Crack on the Stability of a Red Bed Slope: A Case Study in Yunnan Province - Zhenping Zhang; Xiaodong Fu; Qian Sheng; Dawei Yin; Yongqiang Zhou; Juehao Huang (Advances in Civil Engineering)
Red bed slopes in the southwest of China are associated with a grant number of geological hazards, such as landslides, mud-rock flows, and rock blocks falling, which are vital problems in geotechnical engineering. The damage can be induced or triggered due to a series of human and environmental activities, such as excavation, concentrated or long-term rainfall, earthquake, and fluctuation of groundwater level. According to the field observations and geological exploration results, a small-scale landslide was observed on January 10, 2016, after excavation along XiaoMo highway in Yunnan Province. A numerical model in actual size using GeoStudio software based on this typical red bed engineering slope was established in this study. Back analyses and laboratory tests were used to obtain the mechanical parameters of the geomaterial inside the slope. The historic rainfall data of Mengla County from July to September in 2016 was utilized as the flux boundary in analyzing the seepage variation features and the stability of the engineering slope in the rainy season. One major tension crack was set in the shallow region of the silty clay according to the geology survey to perform the disturbance of excavation on the geomorphology of the slope. Attempts were made to establish the anisotropic permeability of the crack induced by the complex fillings, and differences in the hydraulic response between the cracking and completed slope during the rainfall process were discussed. The result shows that the factor of safety of the slope without crack before the rainfall is 1.076, and the slope is considered in the state of the critical limit equilibrium, which is in accordance with the previous state of the slope under real conditions. The pore water pressure variations of the monitor points in the shallow region of the completed slope present close compliance with the rainfall intensity subjected to different rainfall patterns, which also controls the distribution of the plastic zone in the slope after rainfall. The comparisons in the seepage field and plastic zone between the cracking and completed slope reveal that the crack can shorten the infiltration path effectively, and the higher the permeability coefficient in the vertical direction is, the larger the pore water pressure increasing zone is and the higher the underground water level is, which should be paid more attention in highway constructions.